2002
DOI: 10.1055/s-2002-38247
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Antihypertensive Treatment with Perindopril, Pindolol or Felodipinon Plasma Leptin Concentration in Patients with Essential Hypertension

Abstract: First, patients with essential hypertension are characterized by higher plasma leptin levels as compared with normotensive healthy subjects; second, suppressive effect of pindolol on leptinemia may be of pathophysiological relevance in the course of weight gain during beta-blocker therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
(37 reference statements)
0
11
1
Order By: Relevance
“…In sucrose-fed spontaneously hypertensive rats, Ang II receptor antagonists have been shown to reduce plasma L and L mRNA in adipose tissue (23,34), but data are lacking about the effects of these drugs in humans. In patients with essential hypertension, Ficek et al observed that therapy with the Ang II converting enzyme inhibitor perindopril or the CCB felodipine did not influence leptinemia, whereas the β-blocker pindolol significantly decreased it (24). In the present study, unlike felodipine, valsartan produced a significant reduction in plasma L levels.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…In sucrose-fed spontaneously hypertensive rats, Ang II receptor antagonists have been shown to reduce plasma L and L mRNA in adipose tissue (23,34), but data are lacking about the effects of these drugs in humans. In patients with essential hypertension, Ficek et al observed that therapy with the Ang II converting enzyme inhibitor perindopril or the CCB felodipine did not influence leptinemia, whereas the β-blocker pindolol significantly decreased it (24). In the present study, unlike felodipine, valsartan produced a significant reduction in plasma L levels.…”
Section: Discussioncontrasting
confidence: 48%
“…Both dihydropyridine calcium channel blockers (CCBs) and angiotensin (Ang) II type 1 (AT1)-receptor antagonists are suitable for the treatment of obesity-hypertension, since they are devoid of adverse metabolic effects (21). However, contrasting findings have been reported in the literature with regard to their influence on sympathetic activity (22) and few studies have evaluated their effects on plasma L (23,24). With this background, the present study aimed to evaluate the effects of the AT1-receptor antagonist valsartan (25) as compared to the CCB felodipine (26) on plasma L, plasma norepinephrine (NE) and insulin sensitivity in the treatment of hypertensive obese patients.…”
Section: Introductionmentioning
confidence: 99%
“…Certain antihypertensive medications, such as angiotensin receptor blockers, 28 angiotensin-converting enzyme inhibitors 29 and ␤-blockers, 30 have been reported to lower plasma leptin levels. Because antihypertensive medication use was one of the criteria to define hypertension, it is possible that the observed association in our study between leptin and hypertension may be an underestimation of the true association.…”
Section: Discussionmentioning
confidence: 99%
“…However, pindolol markedly suppresses leptin levels without influencing insulin levels. 97 In obese patients with mild to moderate essential hypertension, felodipine has no effect on plasma leptin and insulin sensitivity. However, valsartan significantly reduces plasma leptin, insulin resistance, and BMI.…”
Section: Renin-angiotensin System Blocking Agentsmentioning
confidence: 99%
“…99 Pindolol has a marked suppressive effect on leptin levels. 97 The effects of other drugs in this class on leptin have not yet been investigated.…”
Section: ␤-Blockersmentioning
confidence: 99%